Teacher-student perspective on teaching strategies and constructivist pedagogical skills in master's programs of a Peruvian public university.: Perspectiva docente-estudiante sobre estrategias de enseñanza y habilidades pedagógicas constructivistas en programas de maestrías de una universidad pública peruana - Campos Gutierrez, Janet Pilar (2021)
Introduction: This research addresses the evaluation of teacher performance through the student-centered paradigm. Objective: To determine the teaching strategies and pedagogical skills with a constructivist approach used, from the teacher and student perspective, in the health master's programs of a Peruvian public university. Methodology: Quantitative, descriptive and cross-cutting study. Based on the Evaluation Questionnaire of the Teaching and Evaluative Methodology of University Professors (CEMEDEPU), an instrument was developed, which was validated by expert judgment with an Alpha cronbach reliability of 0.961, which was applied to teachers and students. The sample obtained was from 42 teachers and 130 students from eight master's degrees. The descriptive analysis was performed by categorizing the results in each group and the inferential analysis using the T-student test. Results: Predominated teachers over the age of 56 (55%), with the degree of master (61.9%); students under the age of 40 (79.2), who referred to the research subject when answering the questionnaire. (52.2%). Constructivist teaching strategies, according to the teacher, were regularly used (42.9%) and of low student use (52.6%) while constructivist pedagogical skills were acceptable (66.7%) according to the teacher in contrast to students who were not acceptable (42.3%). Conclusion: Significant difference was found in teaching strategies and pedagogical skills of constructivist approach between teachers and students.